Do pre-admonition suggestions moderate the effect of unbiased lineup instructions? - Quinlivan, Deah S. (Legal and criminological psychology, 2012)
We examined the additive and interactive effects of pre-admonition suggestion and lineup instructions (biased or unbiased) on eyewitness identification rates. Participants watched a mock crime video, completed a target-absent lineup identification, and completed a retrospective memory questionnaire. Prior to attempting an identification, participants were either exposed or not exposed to pre-admonition suggestions and received biased or unbiased lineup instructions. The pre-admonition suggestion indicated that it was likely that the perpetrator was in the lineup (surely, you can pick the perpetrator). The pre-admonition suggestion increased false identification in the unbiased lineup condition. Furthermore, those who received the pre-admonition suggestion were more certain in their identifications as well as other testimony-relevant judgments than were those who did not receive the pre-admonition suggestion. These results suggest that pre-lineup suggestion can mitigate the beneficial effects of unbiased lineup instructions.